Penerimaan Orang Tua Etnis Jawa Pada Penderita Skizofrenia - Bhina Hangudio Hutama Barapinta (Fakultas Psikologi Universitas Negeri Malang, 2020)
The largest schizophrenic sufferers in Indonesia are located on the island ofJava, precisely in East Java and Central Java, are still directly proportional,among the large number of sufferers there are still many who are in pasung,this is what inspires researchers to look further, some of the parents ofsufferers who are able to choose not to be confined and accept the conditionof her child who suffers from schizophrenia. This study aims to find out howthe attitude of ethnic Javanese parents towards their children who suffer fromschizophrenia, what is the form of acceptance and what is the role of culturein encouraging the emergence of such acceptance. The research was carriedout using an ethnographic case study model. The results of the study foundthat the acceptance of Javanese ethnic parents was shown by caring, loving,supportive, caring for children, and being willing to be physically close totheir children. In Javanese terms, this behavior appears in 3 ways, namelygiving in, being patient, and educating.